Consultation and Mediation to Resolve Illegitimate Child Disputes by Prioritizing the Best Interest of the Child Principle - Reynaldi, Richard Dwiky; Sumartono, Nike Natasya Dewi; Pramadani, Indah Septiana; Maryani, Indah; Pratama, Albert Dicky (The Indonesian Journal of International Clinical Legal Education, 2022)
Based on the convention on children's rights, there are four categories of children's rights to realize the principle of the best interest of the child, namely the right to survival, the right to protection, the right to grow and develop, and the right to participate in expressing opinions in all matters affecting children. The right to survival of children requires the state to ensure their survival, both with a conducive environment, decent living facilities and infrastructure to access to basic needs. The principle of the best interest of the child requires child protection providers to look at and make decisions regarding the future of the child based on the child's point of view not the point of view of adults so as to reach and ensure the fulfillment of children's rights.